HIV Testing for PMTCT in Tanzania: Time to move from ‘Voluntary’ to ‘Mandatory’? - Isangula, Kahabi Ganka; Holmes, Audrey; Brownie, Sharon (Advances in Social Sciences Research Journal, 2015)
Introduction: Every year, many infants are infected with HIV, mostly in sub-Saharan Africa. This is predominantly attributed to mother-to-child or “vertical” transmission during pregnancy, labor and delivery, and breastfeeding. Advances in antiretroviral therapy (ART) and funding have made the prevention of mother-to-child transmission (PMTCT) of HIV more affordable in sub-Saharan Africa. However, despite this advance and its potential in PMTCT, the uptake of HIV testing among pregnant women as an entry point to PMTCT services remains unsatisfactory in many countries. Methods & Results: In the present paper, authors’ present a viewpoint that supports mandatory HIV testing for pregnant women and argue that a mandatory HIV testing policy should be adopted in Tanzania. The ongoing debate about implementing mandatory HIV testing for all pregnant women is discussed in terms of a parental obligation towards protecting a newborn child. Evidence for mandatory HIV testing in prisons (e.g., for prostitution related crimes and sexual offenses), as well as mandatory pre-marriage testing is considered. The way in which the legal framework in Tanzania could support mandatory testing is discussed. Conclusion: Authors’ highlight how a national policy of mandatory HIV testing will increase the enrollment of pregnant women into PMTCT services, minimize the risk of HIV transmission to newborn children, improve health outcomes for both parents and children, and contribute to reducing the burden on limited health resources.